Multivariate Insight into Soil Organic Matter Dynamics in Subarctic Abandoned Farmland by the Chronosequence Approach - Timur Nizamutdinov; Sizhong Yang; Xiaodong Wu; Vladislav Gurzhiy; Evgeny Abakumov (Agronomy)
Agricultural land abandonment is a widespread phenomenon found in many regions of the world. There are many studies on post-agricultural changes in temperate, arid, semi-arid regions, etc., but studies of such soils in boreal or Arctic conditions are rare. Our study aims to fill the gaps in research on the processes of post-agricultural soil transformation, with a focus on the harsh climatic conditions of the Arctic and Subarctic regions. Parameters of soil organic matter (SOM) are largely reflected in the quality of soil, and this study investigates the dynamics of SOM properties in Subarctic agricultural soils in process of post-agrogenic transformation and long-term fertilization. Using a chronosequence approach (0–25 years of abandonment) and a reference site with over 90 years of fertilization, we performed elemental (CHN-O) analysis, solid-state 13C NMR spectroscopy of SOM, PXRD of soil and parent material, and multivariate statistical analysis to identify the connections between SOM composition and other soil properties. The results revealed transient increases in soil organic carbon (SOC) during early abandonment (5–10 years; 3.75–4.03%), followed by significant declines after 25 years (2.15–2.27%), driven by mineralization in quartz-dominated soils lacking reactive minerals for organo-mineral stabilization. The reference site (the Yamal Agricultural Station) maintained stable SOC (3.58–3.83%) through long-term organic inputs, compensating for poor mineralogical protection. 13C NMR spectroscopy highlighted shifts from labile alkyl-C (40.88% in active fields) to oxidized O-alkyl-C (21.6% in late abandonment) and lignin-derived aryl-C (15.88% at middle abandonment), reflecting microbial processing and humification. Freeze–thaw cycles and quartz dominance mineralogy exacerbated SOM vulnerability, while fertilization sustained alkyl-C (39.61%) and balanced C:N (19–20) ratios. Principal Component Analysis linked SOC loss to declining nutrient retention and showed SOM to be reliant on physical occlusion and biochemical recalcitrance, both vulnerable to Subarctic freeze–thaw cycles that disrupt aggregates. These findings underscore the fragility of SOM in Subarctic agroecosystems, emphasizing the necessity of organic amendments to counteract limitations of poor mineralogical composition and climatic stress.